2012
DOI: 10.15283/ijsc.2012.5.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stem Cell Therapy on Adriamycin Induced Tubulointerstitial Injury

Abstract: Background and Objectives: It was postulated that adriamycin (ADR) induce renal tubulointerstitial injury. Clinicians are faced with a challenge in producing response in renal patients and slowing or halting the evolution towards kidney failure. The present study aimed at investigating the relation between the possible therapeutic effect of human mesenchymal stem cells (HMSCs), isolated from cord blood on tubular renal damage and their distribution by using ADR induced nephrotoxicity as a model in albino rat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…These results were consistent with Zickri et al [ 5 ] who demonstrated that a single intravenous injection of ADR in rats resulted in a tubulo-interstitial injury in the form of vacuolated cytoplasm, dark nuclei in the cells lining most tubules, detached epithelial cells, and desquamated dark nuclei in the lumina of some tubules. It was postulated that ADR-induced tubular atrophy may be related to the formation of reactive metabolites that attack cell membranes and result in peroxidation of polyunsaturated fatty acids.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were consistent with Zickri et al [ 5 ] who demonstrated that a single intravenous injection of ADR in rats resulted in a tubulo-interstitial injury in the form of vacuolated cytoplasm, dark nuclei in the cells lining most tubules, detached epithelial cells, and desquamated dark nuclei in the lumina of some tubules. It was postulated that ADR-induced tubular atrophy may be related to the formation of reactive metabolites that attack cell membranes and result in peroxidation of polyunsaturated fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…In Group II (ADR group), the rats received a single intravenous injection (tail vein) of ADR at a dose of 5 mg/kg of body weight [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Group II (Adriamycin group), the rats received a single intravenous injection (tail vein) of Adriamycin at a dose of 5 mg/kg of body weight (Montilla et al, 1997) and 1 ml saline 1 week after adriamycin injection. In Group III (adipose‐derived stem cells group), rats received ADMSCs (2 × 10 6 cells suspended in 1 ml saline) 1 week after the Adriamycin injection (Zickri et al, 2012). In Group IV (G‐CSF group), the rats received Adriamycin by the same route and the same dose as Group II, and then G‐CSF was given 2 h after the Adriamycin injection.…”
Section: Methodsmentioning
confidence: 99%
“…Scr26 studies[10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] was included to assess the effect of MSCs on Scr, three for 2 days, four for 3-day, ve for 4 days, six for 5-day, seven for 6-8 days, ten for 10-15 days, six for 28-30 days, and six for ≥ 42days, and the results showed that the difference between MSCs treatment group and control group was…”
mentioning
confidence: 99%